Why evolution is true - Coyne, Jerry A. (New York : Viking, 2009)
Presents the many threads of modern work in genetics, paleontology, geology, molecular biology, and anatomy that demonstrate the indelible stamp of the evolutionary processes first proposed by Darwin.
Bibliografija: str. 251-270.
Kazalo.
Keywords: evolucija